Structure and floristic diversity in permanent monitoring plots in forest ecosystems of Tuscany (Forest Ecology and Management, 2001)
The sampling method is described which is used for the sampling of plant species richness and cover in a monitoring project on forest ecosystems in Tuscany (named MONITO). Species richness is sampled through a nested plot design, with plot size ranging from 1 to 2500 m 2 , whereas species abundance is estimated in 100 m 2 plots. This sampling design is simple to install and to manage through time. Species diversity can be monitored not just at one single spatial scale but at many scales, and species±area relations can also be calculated. The analyses of the data that were collected produced the ®rst available data on species richness in relation to plot size for Tuscan forest ecosystems, indeed for any Italian forests. The Arrhenius Power function and the General Root models showed the best ®t. Turkey oak (Quercus cerris) woods located on slightly acidic soil were found to be the forest ecosystems with the highest species richness, con®rming and quantifying well-established ¯oristic- phytosociological knowledge. Habitat heterogeneity, measured by plot ¯oristic resemblance, showed how the Turkey oak woods were the most heterogeneous at the smaller spatial scales, but not at larger ones